The coconut oil miracle [compact disc, unabridged] - Fife, Bruce, 1952- (Tantor Audio, 2015)
Now in its fifth edition, this revised and updated version has even more information on the benefits of coconut oil and shows listeners how to use it for maximum effect. Bruce Fife shares crucial information, including the latest studies on links between coconut oil and benefits relating to heart function, Alzheimer's prevention, bodily detoxification, weight loss, and many other hot topics.